2008
DOI: 10.3731/topologica.1.015
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Orbital Angular Momentum Transfer between Acoustic and Optical Vortices in Optical Fiber

Abstract: The "Virtual Paper" section provides hyperlinks to already published papers in other journals, which are selected by the editors as excellent papers in topological science and technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In contrast to other optomechanical systems that typically involve standing-wave mechanical vibrations, here circulating phonons comprises the acoustic WGMs 13,22 , which are essentially acoustic vortices [40][41][42] . These travelling-wave type acoustic modes carry angular momentum, which creates possibility of using mFOM devices to enable optomechanical interactions with vortices in various liquids [43][44][45] and condensates.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other optomechanical systems that typically involve standing-wave mechanical vibrations, here circulating phonons comprises the acoustic WGMs 13,22 , which are essentially acoustic vortices [40][41][42] . These travelling-wave type acoustic modes carry angular momentum, which creates possibility of using mFOM devices to enable optomechanical interactions with vortices in various liquids [43][44][45] and condensates.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the lowestloss and compact means to obtain vortices with high modal purity directly from fibers have involved inducing the required mode transformations in the fiber itself. This has been demonstrated with fiber gratings [24] or adiabatic mode couplers [25]. In both cases, immediately after the mode-converter (i.e., within < 3 cm of the rigidly held fiber), a radially or azimuthally polarized beam is obtained.…”
Section: Fiber Generation and Mode Stabilitymentioning
confidence: 99%
“…In addition, given the helical symmetry of these modes, helecoidal gratings in photonic crystal fibers [29], and helically phased inputs into multicore fibers [30] have had success in producing states that resemble the first non-zero OAM state in short ( < 1 m) fibers. One of the lowest loss, high purity techniques to generate OAM in fiber remains acoustooptic gratings [24] mentioned earlier. Akin to the use of doped fibers to achieve radially polarized outputs, mJ energy level lasers with OAM output have been realized using pressure induced mode transformations in a laser cavity [31].…”
Section: Fiber Generation and Mode Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The LP 11 family modes comprise four vector modes; TE 01 , HE 21 even , HE 21 odd , and TM 01 , and it can be shown that the coherent superposition of two vector modes (i.e. HE 21 even and HE 21 odd , TE 01 and TM 01 ) with ±π/2 phase difference between them will lead to circularly-polarized optical vortex beams carrying ±ℏ of OAM per photon [1]. In the scalar approximation, the optical vortex beams can be considered as a linear combination of two orthogonal two-lobed LP 11 modes with ±π/2 phase shift between them, which was demonstrated in a passive multi-mode fiber [2] and an Yb-doped fiber amplifier [3], where the phase shift was achieved by induced stress.…”
Section: Introductionmentioning
confidence: 99%